Studying the Effect of Operating Parameters on the Removal of Nickel Ion from an Adsorber by Using COMSOL Multiphysics Simulation - Hathal, Mustafa M; Hasan, Basim O (Al-Nahrain Journal for Engineering Sciences, 2020)
The heavy metals are considered dangerous pollutants which harm health and environment. The adsorption process is the cost effective process to get-rid of heavy metal efficiently.  In this study, the adsorption bed of Nickel is simulated by using COMSOL Multiphysics to find the effect of different operating parameters namely; flow rate, temperature and pollutant concentration on adsorption bed efficiency.  The modeling of non-isothermal adsorption bed based on experimental isotherms kinetic of previous work is developed too. The results showed that the optimal conditions to generate maximum removal efficiency of heavy metal were at 50?C inlet temperature, 0.1 M inlet concentration, and 80 ml/min flow rate to achieve removal values higher than 50 % of long operation period time.